Preeclamptic programming unevenly perturbs inflammatory and renal vasodilatory outcomes of endotoxemia in rat offspring: modulation by losartan and pioglitazone - Morgaan, Hagar A.; Sallam, Marwa Y.; El-Gowelli, Hanan M.; El-Gowilly, Sahar M.; El-Mas, Mahmoud M. (Frontiers in Pharmacology, 2023)
Introduction: Preeclampsia (PE) enhances the vulnerability of adult offspring to serious illnesses. The current study investigated whether preeclamptic fetal programming impacts hemodynamic and renal vasodilatory disturbances in endotoxic adult offspring and whether these interactions are influenced by antenatal therapy with pioglitazone and/or losartan. Methods: PE was induced by oral administration of L-NAME (50 mg/kg/day) for the last 7 days of pregnancy. Adult offspring was treated with lipopolysaccharides (LPS, 5 mg/kg) followed 4-hr later by hemodynamic and renovascular studies. Results: Tail-cuff measurements showed that LPS decreased systolic blood pressure (SBP) in male, but not female, offspring of PE dams. Moreover, PE or LPS reduced vasodilations elicited by acetylcholine (ACh, 0.01-7.29 nmol) or N-ethylcarboxamidoadenosine (NECA, 1.6-100 nmol) in perfused kidneys of male rats only. The latter effects disappeared in LPS/PE preparations, suggesting a postconditioning action for LPS against renal manifestation of PE. Likewise, elevations caused by LPS in serum creatinine and inflammatory cytokines (TNFα and IL-1β) as well as in renal tubular protein expression of monocyte chemoattractant protein-1 (MCP-1) and AT1 receptors were attenuated by the dual PE/LPS challenge. Gestational pioglitazone or losartan reversed the attenuated ACh/NECA vasodilations in male rats but failed to modify LPS hypotension or inflammation. The combined gestational pioglitazone/losartan therapy improved ACh/NECA vasodilations and eliminated the rises in serum IL-1β and renal MCP-1 and AT1 receptor expressions. Conclusion: Preeclamptic fetal programming of endotoxic hemodynamic and renal manifestations in adult offspring depends on animal sex and specific biological activity and are reprogrammed by antenatal pioglitazone/losartan therapy.